Hubungan Kejadian Depresi Dengan Sindroma Dispepsia Pada Mahasiswa Prodi Kedokteran Umum FKKH Universitas Nusa Cendana - Theedens, Juan Ch. P.; Setianingrum, Elisabeth Levina Sari; Folamauk, Conrad Liab Hendricson; Lidia, Kartini (Universitas Nusa Cendana, 2023)
Background: Depression is a mood disorder that impacts an individual’s neuroendocrine system and overall quality of life. Depression on a medical student will hinders academic performance and is able to stay undetected and affect their professionalism as a doctor in the future, which then lowers the quality of service and the patient’s safety as a whole. Due to the neuroendocrine disturbances, depression can also cause somatic symptoms where the most common symptom found is dyspepsia. Dyspepsia impacts main aspects of quality of life meaning that comorbidity with depression often results in drastic decline in one’s quality of life. Purpose: To assess the correlations of depression and dyspepsia in students of the general medicine program at the faculty of medicine and veterinary of Nusa Cendana University. Method: The method in this study is observational analytic with a cross sectional approach. Data in this study was collected using the Patient Health Questionnaire (PHQ-9 and The Rome III Criteria to screen for depression and functional dyspepsia accordingly. Data analysis was done using the Contingency Coefficient Test. Result: The bivariate analysis conducted showed no significant correlation between depression and dyspepsia in students of the General Medicine Program (p=0.720) at the Medicine and Veterinary Faculty of Nusa Cendana University. Conclusion: There was no significant correlation between depression and dyspepsia in students of the General Medicine Program at the Medicine and Veterinary Faculty of Nusa Cendana University.